2022
DOI: 10.1111/dar.13500
|View full text |Cite
|
Sign up to set email alerts
|

The perceived social rejection of sexual minorities: Substance use and unprotected sexual intercourse

Abstract: This study presents associations between the perceived social rejection of sexual minorities and tobacco, alcohol, and cannabis consumption and unprotected sexual intercourse in the capital of Greece, Athens. This is the first Greek study to evaluate the concept of the minority stress theory on sexual minorities' substance use and unprotected sexual intercourse. In addition, this is among the first international studies to examine whether periods of adverse economic conditions are associated with sexual minori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…The research team consisted of a principal investigator and two research assistants. The principal investigator had accumulated experience in collecting cross-sectional and longitudinal data from vulnerable adult population groups identified in Athenian streets, e. g., sex workers, homeless people, and illicit drug users (Drydakis, 2022a), migrant and refugee groups (Drydakis, 2021(Drydakis, , 2022b, young population groups enrolled in schools (Drydakis, 2023a(Drydakis, , 2023b, sexual orientation minorities (Drydakis, 2022c(Drydakis, , 2022d, and the general public (Drydakis, 2015).…”
Section: Data Gatheringmentioning
confidence: 99%
“…The research team consisted of a principal investigator and two research assistants. The principal investigator had accumulated experience in collecting cross-sectional and longitudinal data from vulnerable adult population groups identified in Athenian streets, e. g., sex workers, homeless people, and illicit drug users (Drydakis, 2022a), migrant and refugee groups (Drydakis, 2021(Drydakis, , 2022b, young population groups enrolled in schools (Drydakis, 2023a(Drydakis, , 2023b, sexual orientation minorities (Drydakis, 2022c(Drydakis, , 2022d, and the general public (Drydakis, 2015).…”
Section: Data Gatheringmentioning
confidence: 99%
“…Furthermore, there are critical economic disparities among individuals based on their sexual orientation and gender identity (Drydakis, 2022b(Drydakis, , 2022c. Due to stigma, social rejection, discrimination and victimisation, LGBT individuals experience higher rates of unemployment, poverty and financial hardships, which have been found to adversely affect their physical and mental health outcomes (Drydakis, 2022b(Drydakis, , 2022c.…”
Section: Socioeconomic Characteristics At the Individual-level Demogr...mentioning
confidence: 99%
“…In Greece, since 2010, research has found that women, disabled people, ethnic minorities, sexual and gender identity minorities, unemployed people, those experiencing low income, disadvantaged populations and people consuming illicit drugs face deteriorated physical and mental health (Drydakis, 2015(Drydakis, , 2021a(Drydakis, , 2022a(Drydakis, , 2023(Drydakis, , 2022b(Drydakis, , 2022c. The empirical evidence reviewed indicates that gender, age, ethnicity, sexual orientation, gender identity, employment, long-term health conditions, substance use and geography might emerge as crucial categories for the study of health determinants and inequalities in populations facing severe economic struggles (Drydakis, 2022a(Drydakis, , 2022b(Drydakis, , 2022c. Multiple marginalisations are mutually constituted and cannot be understood or ameliorated by approaches that treat single socioeconomic characteristics, that is, gender and low-income, as distinct subjects of inquiry (Gkiouleka et al, 2018).…”
Section: Socioeconomic Characteristics At the Individual-level Demogr...mentioning
confidence: 99%
“…During an economic recession, economically unstable families may suddenly find themselves caught in the poverty trap and experience well-being deteriorations (Alemán-Díaz et al 2016;Fanjul 2014;Currie 2009). In Greece, during the economic recession, vulnerable population groups experienced physical health and mental health deterioration (Drydakis 2022a(Drydakis , 2022b2021a, 2021b.…”
Section: Outcomes' Evaluationmentioning
confidence: 99%